Critical review of renewable generation datasets and their implications for European power system models. (December 2021) - Kies, Alexander; Schyska, Bruno U.; Bilousova, Mariia; El Sayed, Omar; Jurasz, Jakub; Stoecker, Horst
Abstract: In the process of decarbonization, the global energy mix is shifting from fossil fuels to renewables. To study decarbonization pathways, large-scale energy system models are utilized. These models require accurate data on renewable generation to develop their full potential. Using different data can lead to conflicting results and policy advice. In this work, several datasets that are commonly used to study the transition towards a highly renewable European power system are compared. Significant differences between these datasets are found, resulting in cost-differences of about 10%. These findings indicate that much more attention must be paid to the large uncertainties of the input data. Graphical abstract: Image 1 Highlights: State-of-the-art datasets that provide country-level renewable generation data are compared. The compared datasets differ significantly with respect to average capacity factors. Differences in levelized cost of electricity based on different datasets can reach about 10%. The choice of the dataset can impact policy advice significantly.